Financial Performance Against Stock Prices of the Mining Sector in Indonesia - Madiha, Fathinul; Fatihudin, Didin; Roosmawarni, Anita (PT. Global World Scientific, 2025)
This study aims to analyze the effect of financial performance on the stock price of mining sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2012–2015. The independent variables in this study consist of Return on Assets (ROA), Return on Equity (ROE), Earnings Per Share (EPS), Price-to-Earnings Ratio (PER), and Price-to-Book Value (PBV). In contrast, the dependent variable is the stock price. The study population includes all mining sector companies listed on the IDX, with samples obtained through a purposive sampling method. The data analysis technique employed is multiple linear regression analysis, which tests the simultaneous and partial effects of each variable on stock prices. The results of the hypothesis testing indicate that all financial performance variables have a significant effect on stock prices simultaneously. To some extent, EPS, ROA, and PBV have a significant impact on stock prices, while ROE and PER do not exhibit a significant effect. EPS was found to be the most dominant variable in influencing the stock prices of mining sector companies. Theoretically, these results strengthen the existing literature on the importance of EPS indicators in stock valuation. At the same time, they provide guidance for investors in making informed investment decisions based on fundamental analysis. This study also suggests the need for a sector-specific approach in evaluating the effect of financial indicators on stock prices.